Nondestructive testing and defectoscopy based on thermal imaging active thermography - Прохоренко, Евгений Михайлович; Базалєєв, Микола Іванович; Бандурян, Борис Багдасарович; Брюховецький, Василь Володимирович; Клепіков, В'ячеслав Федорович; Литвиненко, Володимир Вікторович (Eastern-European Journal of Enterprise Technologies, 2014)
The possibility of identifying defects, based on thermoacoustic effects and their manifestation in the field of infrared radiation by methods of active thermography has been substantiated. The results of experimental researches of detecting defects and structural changes in the material of the object under study by the thermalimaging control under the thermal and acoustic activated influence are given. The effectiveness of applying the proposed method of detecting defects is considered. The value of the conducted researches lies in the fact that the application of an activating external action allows identifying the degradation of thermophysical properties of materials within a defective area, differentiating the origin of temperature anomalies and taking into account the effect of external parameters,which create false thermal anomalies under the thermalimaging control. The developed method can be applied both in conditions of bench tests, and in cases of equipment materials remaining under the influence of process cyclic loadings.